Pendidikan pemilih bagi pemula dalam menciptakan pemilih melek politik di Kabupaten Lampung Selatan dan Kota Bandar Lampung pada Pilkada serentak 2020 - Himawan Indrajat; Arizka Warganegara; Robi Cahyadi Kurniawan; Budi Kurniawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
This community service provides voter education to first-time voters in Bandar Lampung City and Lampung Selatan Regency. In December these two regencies/cities will hold a regional head election simoustanly. It is hoped that by providing voter education, the level of voters political knowledge can increase will not only understand their rights as citizens to vote but also understand the aims and objectives of the elections, understand democracy, regional head elections, and political participation so that new voters hope to become smart and politically literate voters. This service was carried out to assess the knowledge and understanding of the seminar participants using an initial evaluation by filling out an online questionnaire via google form. This method is used to determine the level of knowledge and understanding of participants about democracy, regional elections, and political participation. As well as providing seminar materials related to regional elections, political participation, and public policy. Final evaluation through discussion on issues that have not been understood related to the material presented and the increase in participant knowledge. The number of participants for the voter education service for beginners is 40 people is carried out online through the Zoom application and face-to-face physical because of the COVID-19 pandemic conditions and also because of the service location is in two places and carried out at the same time. Many participants do not know that in December, the regional elections will hold simultaneously. And there are still participants who think that voting during the elections is an obligation as a citizen, not a citizen's right. And there are always participants who do not know about the election management institutions, namely the General Election Commission and the Election Supervisory Board. In the interest to accept money politics, many new voters are interested in receiving money politics on election day. It shows that some beginner voters are willing to take money politics in the upcoming regional elections, so it is necessary to understand that money politics destroys democracy. After filling in the questionnaire, we provided materials about democracy, regional elections, political participation, and money politics. We offer the understanding to voters that the goal of democracy is to create a government that can provide prosperity to its people, and there are ways to select regional head candidates through elections, so voters must be critical to see the track records and backgrounds of local head candidates so that the correct regional head is elected. true in accordance with the aspirations of society.